COMPETITIVE STRATEGY MODEL FOR PURBALINGGA BATIK - Suliyanto, Suliyanto; Wulandari, Siti Zulaikha; Novandari, Weni (Economic Journal of Emerging Markets, 2011)
Batik Purbaling ga has a promising role to increase society’s welfare in Purbalingga. This study aims at investigating the problems of and formulating a competitive strategy for Purbalingga Batik, using an Analytical Hierarchy Process. It uses Strength, Weaknesses, Opportunities and Threats and Quantitative Strategic Planning Matrix to formulate a competitive strategy for Purbalingga Batik. It finds that the operational factor, human resources, marketing, financial and business environment are constraints to the formulating process, with operational factor as the dominant one. It suggests that the Strength-Opportunity is the appropriate tool to develop a competitive strategy for Purbalingga Batik. Keywords: Competitive strategy, analytical hierarchy process, quantitative strategic planning matrix, purbalingga batik JEL classification numbers: D21, D22